2020
DOI: 10.21511/ppm.18(3).2020.02
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of financial and economic regulation of land relations in the context of stimulating entrepreneurial activity in the regions of Ukraine

Abstract: Solving the problem of enhancing the efficiency of the financial and economic regulation of land relations contributes to the development of entrepreneurship in Ukraine. The purpose of the paper is to determine new incentives for encouraging entrepreneurial activity by increasing the efficiency of the financial and economic regulation of land relations by local governments. The study is based on applying the method for predicting amounts of local budget revenues in Ukraine from the land tax and lease fees thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
7
0
4
Order By: Relevance
“…These changes cause structural and other swings in various fields of society, in particular, the financial sector, which is one of the first to respond to global challenges. Thus, recent events related to the spread of coronavirus disease (COVID- 19) have clearly demonstrated that all markets around the world have reacted with different in value, but clearly significant changes in financial figures [3][4][5][6][7][8][9][10][11][12]. An important part of the financial sector of the economy is the insurance sector, which is integral to financial stability as a whole [13].…”
Section: Introductionmentioning
confidence: 99%
“…These changes cause structural and other swings in various fields of society, in particular, the financial sector, which is one of the first to respond to global challenges. Thus, recent events related to the spread of coronavirus disease (COVID- 19) have clearly demonstrated that all markets around the world have reacted with different in value, but clearly significant changes in financial figures [3][4][5][6][7][8][9][10][11][12]. An important part of the financial sector of the economy is the insurance sector, which is integral to financial stability as a whole [13].…”
Section: Introductionmentioning
confidence: 99%
“…Fortschritte in Marketing, Sozial Engineering sowie Verbrauchererfahrung und die lebenswichtige Notwendigkeit, Waren zu kaufen, zeigen jedoch, dass diese Entscheidungen manchmal nur eine Illusion sind, da moderne virtuelle Gemeinschaften in der Lage sind, menschliche Wahrnehmungen und Handlungen zu formen und zu verändern. Im heutigen Umfeld und der Teilhabe der Gesellschaft an verschiedenen virtuellen Gemeinschaften lassen sich die Auswirkungen auf das menschliche Verhalten leichter denn je realisieren, da die Bildung menschlichen Verhaltens viel schneller und mit einem viel größeren Publikum realisiert wird [23][24][25][26][27][28][29][30][31][32][33].…”
unclassified
“…Ändern sich die Formen, Methoden der Aufzeichnung, Arten von Medien usw. Die Essenz des Bargelds wird in seiner physischen Form des Geldes als gesetzliches Zahlungsmittel auf einem bestimmten Territorium und die unbaren Form realisiert als Buchführungssystem, das die Aufzeichnungen darüber aufzeichnet, wer wem und wie viel schuldet [27][28][29][30][31][32][33][34]. Modernes sogenanntes Fiat-Geld hat keinen Wert aufgrund der Materialien, aus denen es hergestellt wird (wie Edelmetalle oder andere wertvolle Komponenten), und seine Verwendung basiert ausschließlich auf Vertrauen.…”
unclassified